Ophthalmic Rosai–Dorfman disease: a multi-centre comprehensive study - Tariq A. Alzahem (BMC, 2021)
Abstract Background To provide basic demographic information and clinicopathologic features of ophthalmic Rosai–Dorfman disease (RDD) with a literature review. Methods A multi-centre retrospective case series reviewing all patients with histopathologically confirmed ophthalmic RDD at three tertiary eye care centres between January 1993 and December 2018. Results Eleven eyes of eight patients with histopathologically confirmed ophthalmic RDD were included, with equal numbers of males and females. The median age was 40.25 years (range: 26.6–72.4). Two patients had familial RDD. The orbit was the most commonly involved site (90.9% eyes). One patient (one eye) presented with a scleral nodule, anterior uveitis and cystoid macular oedema. Visual acuity ranged from 20/25 to light perception. Six patients had an extra-nodal ophthalmic disease, and the remaining two had an associated submandibular lymphadenopathy (nodal RDD). Conclusions Ophthalmic RDD can be the only manifestation of this systemic disease, with the orbit being the most commonly involved site, exhibiting bone destruction, intracranial and/or sinus involvement and variable degree of visual loss. Ophthalmic familial RDD represent a severe form with a malignant course. Steroid monotherapy may be inadequate to control orbital RDD; thus, combined treatment is usually necessary. A comprehensive approach to assessment and management is recommended.